Previous flight facilitates partner finding in female crickets - Maxim Mezheritskiy (Nature Portfolio, 2020)
Abstract In the cricket Gryllus bimaculatus, flying occurs soon after the last imaginal molt and precedes the mating behavior in natural conditions. Here, we tested the hypothesis that flying may improve subsequent behavioral performance in a novel environment in female crickets. We developed a behavioral set-up to test female cricket responsiveness to male calling song as well as their ability to locate and find the source of the song. The male song was produced by a loudspeaker hidden behind the fabric wall of a spacious square arena. Forced flight prior to the test promoted female sexual searching behavior in the novel environment. After the flight, more females reached the hidden source zone, spent more time near the source and finally more of them climbed over the wall section immediately in front of the hidden loudspeaker. At the same time, their behavior in the arena did not differ from the control group when the calling song was not delivered, suggesting that flight exerts its behavioral effects by influencing sexual motivation. Our results support the suggestion that preceding intense locomotion facilitates sexual searching behavior of females in a novel environment.